FAKTOR LINGKUNGAN SOSIAL YANG BERHUBUNGAN DENGAN TINGKAT KEPATUHAN TERAPI PENDERITA HIPERTENSI PRIMER DI PUSKESMAS KEDUNGMUNDU KOTA SEMARANG (Social Environment Factors Associated with The Level of Compliance Therapy in Patients with Primary Hypertension - Binti Sabrina; Henry Setyawan Susanto; Mateus Sakundarno Adi (Jurnal Kesehatan Masyarakat (Undip), 2017)
Compliance is the level of patient behavior against instruction given by health workers. According WHO reports in 2003, medication adherence to long-term therapy patients with chronic disease in developed countries by 50% and in developing countries was expected to lower. In the Semarang, Kedungmundu was the areas with the highest incidence of hypertension (5,83%), 62,7% of 75 patients did not routine check. The purpose of this research was to know the factors associated with the compliance therapy of patients with primary hypertension. A kind of study was observational analytic with cross sectional design. Subject of study was 148 patients with primary hypertension. The sampling method used was consecutive sampling. The univariate analysis show that 45,3% patients compliance and 54,7% patients non compliance. The bivariate analysis used chi square test with 5% level of significance shows that therapeutic communication (POR=36,8; p=<0,001), family support (POR=32,7; p=<0,001), health worker support (POR=20,7; p=<0,001), income (POR=6,5; p=<0,001), and other treatment (POR=7,3; p=<0,001) associated with level of compliance. The multivariate analysis show that therapeutic communication (p=<0,001), family support (p=0,001) and income (p=0,002) impact on the compliance level therapy. From the result was concluded that therapeutic communication, the family support and income influence to the compliance level therapy of patients with primary hypertension in Kedungmundu. Advice was given to family to increase the role of patients therapy, health workers to modify the information and next researchers to choose other sampling method and measuring instrument.